2012
DOI: 10.1186/1471-2180-12-35
|View full text |Cite
|
Sign up to set email alerts
|

Potential serodiagnostic markers for Q fever identified in Coxiella burnetiiby immunoproteomic and protein microarray approaches

Abstract: BackgroundCoxiella burnetii is the etiological agent of Q fever. The clinical diagnosis of Q fever is mainly based on several serological tests. These tests all need Coxiella organisms which are difficult and hazardous to culture and purify.ResultsAn immunoproteomic study of C. burnetii Xinqiao strain isolated in China was conducted with the sera from experimentally infected BALB/c mice and Q fever patients. Twenty of whole proteins of Xinqiao recognized by the infection sera were identified by mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 32 publications
2
79
0
2
Order By: Relevance
“…Therefore, we speculate that these proteins might be the most presented antigens to immune cells due to high abundance during activated metabolism. This assumption is in good agreement with the result of Xiong et al (2012a) who evaluated potential serodiagnostic markers for Q fever and identified 13 proteins with housekeeping function out of 20 antigenic proteins. They discovered that proportionally more of these proteins are recognized by the sera from patients with acute rather than with chronic or persistent infections.…”
Section: Figsupporting
confidence: 76%
See 4 more Smart Citations
“…Therefore, we speculate that these proteins might be the most presented antigens to immune cells due to high abundance during activated metabolism. This assumption is in good agreement with the result of Xiong et al (2012a) who evaluated potential serodiagnostic markers for Q fever and identified 13 proteins with housekeeping function out of 20 antigenic proteins. They discovered that proportionally more of these proteins are recognized by the sera from patients with acute rather than with chronic or persistent infections.…”
Section: Figsupporting
confidence: 76%
“…Thus, fourteen articles investigated the reactivity of human, seven mice, and one guinea pig sera. Interestingly, one of the selected studies employed two different experimental procedures for evaluating the same human sera (Xiong et al, 2012a). On the other hand, we excluded a publication describing a frequently published antigen which was recognized by sera from experimentally and naturally infected goats, since it did not report a screening method (Fernandes et al, 2009).…”
Section: Selection Of Immunoproteomic Publicationsmentioning
confidence: 99%
See 3 more Smart Citations